PENINGKATAN PENGETAHUAN KELEGISLATIFAN KADER MUDA DPD PARTAI GOLKAR KABUPATEN BANDUNG - Tatik Rohmawati (JUARA: Jurnal Wahana Abdimas Sejahtera, 2022)
Community Service activities (PKM) are aimed at opening wider knowledge about legislation among cadres, getting young cadres who are knowledgeable, reliable and understand the legislative developments that are developing in the Indonesian government and to grow future leaders who are good and right in the legislature. The method used is a lecture through a webinar by providing material on the Democratic Legislative Process with participants. The results of this PkM activity for participants can increase knowledge about legislation, raise awareness about the importance of legislative institutions and develop a mindset in legislative matters for the progress of the Indonesian nation. For universities, in this case UNIKOM can collaborate in various fields with the Regional Representative Council (DPD) of Bandung Regency, especially in the Governance Science Study Program, Faculty of Social and Political Sciences. In addition, it can establish relations between institutions and the community can also convey their aspirations to the young cadres of the DPD Golkar Party, Bandung Regency. Young DPD cadres of the Golkar Party know better and increase their knowledge regarding the legislative process. This is known from several questions asked by several participants and the answers given by the participants were quite satisfactory